2020
DOI: 10.1097/prs.0000000000006658
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Fat Reduction with Injected Ice Slurry

Abstract: Background: Cryolipolysis is a noninvasive method for removal of subcutaneous fat for body contouring. Conventional cryolipolysis with topical cooling requires extracting heat from subcutaneous fat by conduction across the skin, thus limiting the amount and the location of the fat removed. The authors hypothesized that local injection of a physiological ice slurry directly into target adipose tissue would lead to more efficient and effective cryolipolysis. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 15 publications
7
51
0
Order By: Relevance
“…These include: (1) the ability to inject the slurry using a hypodermic needle and syringe; (2) infiltration of the slurry into tissue increases the likelihood of cooling the target nerve; (3) ice slurry is nerve-selective because of its temperature, and although cold enough to cause cryoneurolysis, it is not destructive to other tissue with the exception of adipose tissue. 15 For these reasons, the use of injectable ice…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These include: (1) the ability to inject the slurry using a hypodermic needle and syringe; (2) infiltration of the slurry into tissue increases the likelihood of cooling the target nerve; (3) ice slurry is nerve-selective because of its temperature, and although cold enough to cause cryoneurolysis, it is not destructive to other tissue with the exception of adipose tissue. 15 For these reasons, the use of injectable ice…”
Section: Discussionmentioning
confidence: 99%
“…14 We created a novel method of local tissue cooling, using the phase change properties of ice particles in an ice slurry suspension, and showed that it can safely, selectively, and effectively target lipid-rich tissue in a porcine model. 15 Ice slurries can absorb high quantities of heat, owing to ice's large heat of fusion (334 J/g). In the current study, a biocompatible ice slurry at moderately cold temperatures (around −5°C) and consisting of sterile ice particles suspended in normal saline and glycerol was used to selectively cool a peripheral nerve.…”
Section: Editor's Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…It was first reported in the literature by Garibyan et al in early 2020. 2 A careful review of the literature does not reveal any human trials or FDA-approved use of ice slurry injections for weight-loss. We present the first human case and severe adverse reactions following this new procedure.…”
mentioning
confidence: 99%